Desain Interior Mempengaruhi Minat Pengunjung Restoran Sajian Bhinneka Di Medan - Rani Hermita; Mislida Murti (Jurnal Riset Rumpun Seni, Desain dan Media, 2022)
The restaurant is the most visited place both for meeting friends orfor gathering with family to eat together. So we need a unique interior design to attract visitors. Taking into account the modern layout and interior so as to make visitors more comfortable to relax. The attractiveness of a restaurant can be made in various ways, such as a very unique and attractive interior or exterior design. The purpose of this research is to analyze the influence of interior design on the interest of restaurant visitors. Sampling in this study using simple random sampling technique. Sample random sampling is a technique where sampling is carried out directly at the place to be sampled. An example in this study is the 100 responses that were visitors to a multi-ethnic restaurant in Medan. The technique used in this study uses data analysis techniques to test the validity, reliability and regression tests to test the effect of independent variables on the dependent. Based on the results obtained from an analysis of the positive influence between interior design and the interest of visitors to a diverse serving restaurant in Medan, the better and more attractive the interior design used, the increasing number of visitors coming to a diversity serving restaurant in Medan